2023
DOI: 10.32604/csse.2023.038429
|View full text |Cite
|
Sign up to set email alerts
|

FST-EfficientNetV2: Exceptional Image Classification for Remote Sensing

Abstract: Recently, the semantic classification (SC) algorithm for remote sensing images (RSI) has been greatly improved by deep learning (DL) techniques, e.g., deep convolutional neural networks (CNNs). However, too many methods employ complex procedures (e.g., multi-stages), excessive hardware budgets (e.g., multi-models), and an extreme reliance on domain knowledge (e.g., handcrafted features) for the pure purpose of improving accuracy. It obviously goes against the superiority of DL, i.e., simplicity and automation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In the past 3 years, researchers have proposed various ViT‐based methods for RSI classification, demonstrating remarkable performance compared to CNN‐based approaches. However, several recent studies have suggested that most of these ViT‐based methods cannot outperform their CNN counterparts, particularly when training samples are limited (Song, 2023a, b; Song & Zhou, 2023). Furthermore, these CNN methods possess only one‐tenth or even fewer parameters compared to ViT approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In the past 3 years, researchers have proposed various ViT‐based methods for RSI classification, demonstrating remarkable performance compared to CNN‐based approaches. However, several recent studies have suggested that most of these ViT‐based methods cannot outperform their CNN counterparts, particularly when training samples are limited (Song, 2023a, b; Song & Zhou, 2023). Furthermore, these CNN methods possess only one‐tenth or even fewer parameters compared to ViT approaches.…”
Section: Introductionmentioning
confidence: 99%